2020
DOI: 10.1007/s00264-020-04790-9
|View full text |Cite
|
Sign up to set email alerts
|

What are the outcomes of core decompression without augmentation in patients with nontraumatic osteonecrosis of the femoral head?

Abstract: Purpose Core decompression (CD) of the femoral head is performed to preserve the hip in avascular necrosis (AVN). The outcome following this procedure differs based on the medical centre and the technique. Also, the time to total hip replacement (THR) and the percentage of patients subsequently undergoing a THR are controversial. Methods A systematic review was performed following PRISMA guidelines. The search included CENTRAL, MEDLINE, EMBASE, Sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 68 publications
1
26
1
Order By: Relevance
“…Another meta-analysis also indicated that multiple drilling did not have significantly better effect on the prevention of THA progression than other therapeutic interventions [ 23 ]. The rate of survival following multiple drilling (78.3%) in our cohort appears to be higher than that reported by the majority of previous studies [ 6 , 24 ]. The possible reason may be that the present study included only ONFH hips with modified Ficat and Arlet stage I and II.…”
Section: Discussioncontrasting
confidence: 81%
“…Another meta-analysis also indicated that multiple drilling did not have significantly better effect on the prevention of THA progression than other therapeutic interventions [ 23 ]. The rate of survival following multiple drilling (78.3%) in our cohort appears to be higher than that reported by the majority of previous studies [ 6 , 24 ]. The possible reason may be that the present study included only ONFH hips with modified Ficat and Arlet stage I and II.…”
Section: Discussioncontrasting
confidence: 81%
“…While standard CD was the most widespread joint-preserving procedure proposed in the recent decade, Al Omran [ 28 ] reported that no differences were found in the outcome or complication rate between patients who underwent standard CD and multiple drilling at a mean 3-year follow-up. In our cohort, multiple drilling was used in all included patients of precollapse NONFH with relative better outcomes than prior studies [ 29 , 30 ]. A possible interpretation might include the following: first, multiple drilling with small diameter pin could easily reach the anterior portion of the femoral head reducing intraosseous hypertension; second, the technique was one of the mini-invasive interventions which could reduce the possibility of penetrating the femoral head and damaging the articular cartilage; third, due to the small diameters of drilling, the procedure provided mechanical support, retained the anatomic structure of the femoral head, and reduced the risk of subtrochanteric fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported the advantages of arthroscopy in AVNFH as regards the reduction of THR and improvement of HHS [9,29,31] . Moreover, arthroscopy is preferred over open surgery due to the small incision and minimization of manipulation damage to the articular cartilage as well as its diagnostic role [7,32,33] . As the synthesis of the information is lacking, as far as we know, therefore, the purpose of this review is to explore the efficacy of arthroscopy to salvage hip joints in selected cases and to minimize the need for THR in young adults patients with AVNFH.…”
Section: Othersmentioning
confidence: 99%